Traquest Model: A Novel Model for ACID Concurrent Computations - Rátai, Dániel Balázs; Horváth, Zoltán; Porkoláb, Zoltán; Tóth, Melinda (Acta Cybernetica, 2021)
Atomicity, consistency, isolation and durability are essential properties of many distributed systems. They are often abbreviated as the ACID properties. Ensuring ACID comes with a price: it requires extra computing and network capacity to ensure that the atomic operations are done perfectly, or they are rolled back. When we have higher requirements on performance, we need to give up the ACID properties entirely or settle for eventual consistency. Since the ambiguity of the order of the events, such algorithms can get very complicated since they have to be prepared for any possible contingencies. Traquest model is an attempt for creating a general concurrency model that can bring the ACID properties without sacrificing a too significant amount of performance.